2015
DOI: 10.1371/journal.pntd.0003488
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Antifungal Activity of Sudanese Medicinal Plants against Madurella mycetomatis, the Eumycetoma Major Causative Agent

Abstract: Eumycetoma is a debilitating chronic inflammatory fungal infection that exists worldwide but it is endemic in many tropical and subtropical regions. The major causative organism is the fungus Madurella mycetomatis. The current treatment of eumycetoma is suboptimal and characterized by low cure rate and high recurrence rates. Hence, an alternative therapy is needed to address this. Here we determined the antifungal activity of seven Sudanese medicinal plant species against Madurella mycetomatis. Of these, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…In vitro susceptibility assays can also be used to determine the activity of medicinal plants against mycetoma causative agents. So far the activity of fractions or essential oils from the following plants have been determined: Acacia nubica , 30 Boswellia papyrifera , 30 , 52 Cinnamum verum , 30 Croton zambesicus , 52 Cummium cymimum , 52 Cymbopogon nervatus , 52 Cymbopogon proximus , 52 Cyperus rotundus , 52 Eucalyptus camaldulensis , 52 Eugenia caryophilus , 30 Melaleuca alternifolia , 33 Mentha spicata , 52 Nigella sativa , 30 Ocimum bacilicum , 52 Piper nigrum , 30 Xylopia aethiopica 52 and Zingiber officinalis 30 (Table 5 ). In general, relatively low MICs were obtained for the essential oils (MIC50 ranging from 0.063% to 0.25% v/v).…”
Section: Antifungal Agents Testedmentioning
confidence: 99%
“…In vitro susceptibility assays can also be used to determine the activity of medicinal plants against mycetoma causative agents. So far the activity of fractions or essential oils from the following plants have been determined: Acacia nubica , 30 Boswellia papyrifera , 30 , 52 Cinnamum verum , 30 Croton zambesicus , 52 Cummium cymimum , 52 Cymbopogon nervatus , 52 Cymbopogon proximus , 52 Cyperus rotundus , 52 Eucalyptus camaldulensis , 52 Eugenia caryophilus , 30 Melaleuca alternifolia , 33 Mentha spicata , 52 Nigella sativa , 30 Ocimum bacilicum , 52 Piper nigrum , 30 Xylopia aethiopica 52 and Zingiber officinalis 30 (Table 5 ). In general, relatively low MICs were obtained for the essential oils (MIC50 ranging from 0.063% to 0.25% v/v).…”
Section: Antifungal Agents Testedmentioning
confidence: 99%
“…Lesions consist of a painless subcutaneous mass, presence of sinuses and sero-purulent discharge, colored grains and aggregates of the fungal hyphae. The progression of the disease can lead to the involvement of the skin, deep structures, fascia, and bones with consequent deformity and disability [67][68][69].…”
Section: Fusariosis: Fusariosisis Is Caused By Fusarium Species Inclumentioning
confidence: 99%
“…Previous studies have already demonstrated the ability of different plant extracts and essential oils to inhibit the growth of M . mycetomatis [ 9 , 10 ]. Essential oils are a mixture of multiple, potentially synergistic, compounds which derive from plants as secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%